Magnet® and Pathway to Excellence®: Focusing on Research and Evidence-Based Practice. (May 2020) - Nelson-Brantley, Heather V.; Beckman, Dee; Parchment, Joy; Smith-Miller, Cheryl A.; Weaver, Susan H.
Abstract : Healthcare organizations seeking to achieve or maintain Magnet ® or Pathway to Excellence ® designation are increasingly challenged to demonstrate how nurses are leading or are engaged in research and evidence-based practice. This article describes common barriers to and effective strategies for developing a culture of research and evidence-based practice, with recommendations for Magnet- and Pathway-seeking organizations.